Does unfairness hurt women? The effects of losing unfair competitions - Stefano Piasenti; Marica Valente; Roel van Veldhuizen; Gregor Pfeifer (Lund University, School of Economics and Management, Department of Economics, 2023)
How do men and women dier in their persistence after experiencing failure in a competitive environment? We tackle this question by combining a large online experiment (N=2,086) with machine learning. We find that when losing is unequivocally due to merit, both men and women exhibit a significant decrease in subsequent tournament entry. However, when the prior tournament is unfair, i.e., a loss is no longer necessarily based on merit, women are more discouraged than men. These results suggest that transparent meritocratic criteria may play a key role in preventing women from falling behind after experiencing a loss.
Keywords: C90; D91; J16; C14; 330; Competitiveness; Gender; Fairness; Machine learning; Online experiment